Online and offline communication for country brands: an exploratory study of the Brazil Brand - Kanazawa,Flávio Notomi (2019)
Abstract The fierce international competition among tourist destinations forces their managers to offer their public unique value propositions, seeking to improve their images and highlighting their unique tourist experiences and advantages. In this process, the proper management and communication of a country brand becomes even more relevant. The growing number of people who use the Internet to plan their trips causes country brand managers to be concerned with building a solid digital performance for their brands. In this context, this article sought to understand the management and communication practices developed for the Marca Brasil (Brazil Brand) and its activities on the Internet. To this end, a qualitative and exploratory research was carried out by conducting in-depth, semi-structured interviews with Embratur professionals responsible for the management of the Brazil Brand and its online performance. The results of this article describe the core objectives of the brand, its applications, and the activities developed to achieve them, emphasizing their actions through the Visit Brazil website and its social media channels.